Self-portrait with nothing - Pokwatka, Aimee (Tordotcom/Tom Doherty Associates, 2022)
"Aimee Pokwatka's novel Self-Portrait with Nothing is "fraught and deeply moving...the work of a genuinely exciting new talent." (Booker Prize winner, George Saunders). If a picture paints a thousand worlds... Abandoned as an infant on the local veterinarian's front porch, Pepper Rafferty was raised by two loving mothers, and now at thirty-six is married to the stable, supportive Ike. She's never told anyone that at fifteen she discovered the identity of her biological mother. That's because her birth mother is Ula Frost, a reclusive painter famous for the outrageous claims that her portraits summon their subjects' doppelgangers from parallel universes. Researching the rumors, Pepper couldn't help but wonder: Was there a parallel universe in which she was more confident, more accomplished, better able to accept love? A universe in which Ula decided she was worth keeping? A universe in which Ula's rejection didn't still hurt too much to share? Sometimes living our best life means embracing the imperfect one we already have..."--